Polarized protons acceleration at U-70 - Otboyev, A.V.; Shatunov, P.Yu.; Shatunov, Yu.M. (Вопросы атомной науки и техники, 2006)
A possibility to accelerate polarized proton at the synchrotron U-70 is considered. Estimations of the spin resonances are given in the energy range 2.5…70 GeV. To suppress depolarizing effects of spin resonances, a scheme of three partial Siberian snakes is suggested. Each snake consists from helical magnets with 4.5 T magnetic field. The scheme provides the adiabatic spin flip at imperfection resonances and suppresses all intrinsic resonances by quite realistic beam emittance and magnets misalignments ±5 mm.